2021
DOI: 10.1123/jpah.2020-0525
|View full text |Cite
|
Sign up to set email alerts
|

Global Public Health Guidelines on Physical Activity and Sedentary Behavior for People Living With Chronic Conditions: A Call to Action

Abstract: Background: In 2020, the World Health Organization (WHO) released global guidelines on physical activity (PA) and sedentary behavior, for the first time providing population-based recommendations for people living with selected chronic conditions. This article briefly presents the guidelines, related processes and evidence, and, importantly, considers how they may be used to support research, practice, and policy. Methods: A brief overview of the scope, agreed methods, selected chronic conditions (adults livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 54 publications
1
52
0
1
Order By: Relevance
“…Chronic conditions are addressed separately in both the guidelines and associated publications. 16,22 In many instances, the impairment rather than the health condition per se can impact the exercise response. People living with Parkinson's or a history of stroke (evidence for which was reviewed) can experience difficulties with mobility, motor control, tremors, and paralysis in limbs, which could also be experienced by people living with muscular dystrophy or cerebral palsy.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic conditions are addressed separately in both the guidelines and associated publications. 16,22 In many instances, the impairment rather than the health condition per se can impact the exercise response. People living with Parkinson's or a history of stroke (evidence for which was reviewed) can experience difficulties with mobility, motor control, tremors, and paralysis in limbs, which could also be experienced by people living with muscular dystrophy or cerebral palsy.…”
Section: Resultsmentioning
confidence: 99%
“…In these systematic reviews, physical activity is most frequently reported as steps per day (steps.day -1 ) and no meta-analysis has been conducted on minutes of moderate-to-vigorous intensity physical activity (MVPA) in participants with CVD. Global public health guidelines recommend adults with chronic conditions to do at least 150–300 minutes of moderate-intensity aerobic physical activity (MPA), or at least 75–150 minutes of MVPA per week, or an equivalent combination of both [ 9 ]. Furthermore, adults with chronic conditions should limit the amount of time spent in sedentary behaviour [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global public health guidelines recommend adults with chronic conditions to do at least 150–300 minutes of moderate-intensity aerobic physical activity (MPA), or at least 75–150 minutes of MVPA per week, or an equivalent combination of both [ 9 ]. Furthermore, adults with chronic conditions should limit the amount of time spent in sedentary behaviour [ 9 ]. Patients with CVD should seek to accumulate 6,500 to 8,500 steps.day -1 in order to achieve a physical activity energy expenditure high enough to limit vascular disease progression [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical activity is a recognized cost-effective intervention for public health and is associated with an ever-widening constellation of health, economic, and other benefits, playing an important role in the prevention and management of many major chronic conditions. Thus, the implementation of programs, practices, and policies to facilitate more physical activity and limit sedentary behavior could result in significant health improvements and other benefits, as well as reducing the burden and cost of chronic disease to healthcare systems [1]. In this respect, sedentary behavior is associated with negative changes in the neuromuscular systems of healthy older adults, resulting in a decrease in physical functioning [2].…”
Section: Introductionmentioning
confidence: 99%